Assessing demographic profile on security compliance intention in financial institution / Rohayu Abdul Samad - Abdul Samad, Rohayu (2016)
Information system security compliance advocates a proper guideline during performing task and it also shape user behavior as part of an overall corporate information security management program. A major challenge for corporate organization is encouraging and educating employees to comply with policy and helping them acquire the skills necessary not to violate the policies unconsciously. CIMB Bank as one of the largest financial institutions in Malaysia also has to deal with this information system security compliance since the emerging of unified communication could significantly compromise the information system security compliance. An information system security policy was basically implemented in CIMB Bank but to what extent employees comply with this policy and which factors were chosen to be the significant influence towards compliance. The first objectives of this research to assess demographic profiles in security compliance intention in financial institution by identify using profiles based on age, gender, years working, education and job title against security compliance intention. Second objectives; review the significant impact on demographic profiles against information system security compliance. Third objectives are to suggest recommendation to improve of information system security compliance intention based on demographic profile in financial institution context based on result analysis. The research scope will be financial institution in this case study is CIMB Bank. The methodology that be used is quantitative method. This paper examines the relationship in independent variable (age, gender, years working, education and job title) against security compliance intention as dependant variable. Our result show there is no significant impact in security compliance intention on financial institution. The significant of this research will help to improve the information system security compliance by review the employees profile by identify which group focus in employees that require more intention on information system security compliance. It can be part of contribution for financial institution to use as reference for future research. Index Terms - Information system security, independent variable, dependent variable, regression analysis, security compliance intention.